Analysis of Genetic Diversity and Antibiotic Options for Clinical Listeria monocytogenes Infections in China. (9th April 2021) - Yu, Wei; Huang, Yicheng; Ying, Chaoqun; Zhou, Yanzi; Zhang, Li; Zhang, Jiajie; Chen, Yingsha; Qiu, Yunqing
Abstract: Background: The aim of this study was to investigate the mechanism of Listeria monocytogenes (Lm) pathogenicity and resistance. In addition, the effect of existing treatment options against Lm were systematically evaluated. Methods: Six Lm isolates were collected and antimicrobial susceptibility testing of 15 antibiotics were done. Subsequently, whole genome sequencing and bioinformatics analysis were performed. Biofilm formation was evaluated by crystal violet staining. Furthermore, the effect of meropenem, linezolid, penicillin, vancomycin, and trimethoprim/sulfamethoxazole were determined using the time-kill assay. Results: Four sequence types (STs) were identified (ST1, ST3, ST87, ST451). Multivirulence-locus sequence typing results classified ST87 isolates into cluster. All isolates were resistant to fosfomycin and daptomycin with fosX and mprF . In addition, a total of 80 virulence genes were detected and 72 genes were found in all 6 isolates. Seven genes associated with hemolysin were found in 26530 and 115423. However, due to lack of one genomic island including virulence genes related to flagellar synthesis, isolate 115423 produced less biofilm than 5 other isolates. Although all isolates were susceptible to vancomycin, the in vitro time-kill assay showed that vancomycin monotherapy resulted in less than 2 log10 cerebrospinal fluid (CFU)/mL compared with the initial count. Trimethoprim/sulfamethoxazole at serum or CFU concentrations had bactericidal effect against tested Lm strains at 24 hours. Conclusions: ST87 clone was a typical prevalent ST in clinical Lm isolates in China. Trimethoprim/sulfamethoxazole might be greater potential therapeutic option against Lm infections. Abstract : The present study revealed ST87 clone was the predominant sequence type among clinical Listeria monocytogenes (Lm) isolates in China. Although all isolates were susceptible to vancomycin, the effect was still unsatisfactory. Trimethoprim/sulfamethoxazole was a potent option against Lm infections.